EFFECT OF LEPTIN ON IN-VITRO MATURATION OF OOCYTES AND ON EARLY EMBRYONIC DEVELOPMENT IN BUFFALOES - SINGH, BEERENDRA; PRASAD, SHIV; GUPTA, H P (The Indian Journal of Animal Reproduction, 2023)
The present study was aimed to assess the physiological function of Leptin on in-vitro maturation of oocytes and early embryonic development to increase the efficiency of in-vitroembryo production in buffaloes. The oocytes were maturated in 199 medium supplemented with 10% FBS, 0.51,.1g/ml FSH, 101U/ml LH, 11,.19/ml estradiol-17p, 20ng/ml EGF and 50 μM cysteamine in four groups i.e. Group-I (without leptin), Group-I I (1 Ong/ml leptin), GroupIll (20ng/ml leptin) and Group-IV (30ng/ml leptin) in CO2 incubator at 37°C temperature, 5% CO2 and high humidity. The matured oocytes were fertilized in-vitro in modified synthetic oviductal fluid (mSOF) containing 1 Ong/ml heparin. Presumptive zygotes were cultured in mSOF for 7 days to study embryonic development. The oocytes maturation rates were 76.55, 83.25, 90.14 and 92.16 %, respectively in groups I, II, Ill and IV, cleavage rates were 48.75, 59.77, 70.83 and 71.50%, embryonic development to morula stage were 41.03, 50.96, 58.82 and 57.34%% and blastocyst development rates were 25.64, 30.77, 44.12 and 44.06 %. The oocytes maturation, cleavage, morula and blastocyst development rates were significantly higher in leptin supplemented groups. From the present study, it may be concluded that leptin at the concentration of 20ng/ml in maturation medium significantly (P<0.05) improved maturation rate, cleavage, morula and blastocyst development in buffaloe oocytes.